Assessment of Patterns of Patient-Reported Outcomes in Adults with Congenital Heart disease — International Study (APPROACH-IS): Rationale, design, and methods. (20th January 2015) - Apers, Silke; Kovacs, Adrienne H.; Luyckx, Koen; Alday, Luis; Berghammer, Malin; Budts, Werner; Callus, Edward; Caruana, Maryanne; Chidambarathanu, Shanthi; Cook, Stephen C.; Dellborg, Mikael; Enomoto, Junko; et al.
Abstract: Background: Data on patient-reported outcomes (PROs) in adults with congenital heart disease (CHD) are inconsistent and vary across the world. Better understanding of PROs and their differences across cultural and geographic barriers can best be accomplished via international studies using uniform research methods. The APPROACH-IS consortium (Assessment of Patterns of Patient-Reported Outcomes in Adults with Congenital Heart disease — International Study) was created for this purpose and investigates PROs in adults with CHD worldwide. This paper outlines the project rationale, design, and methods. Methods/design: APPROACH-IS is a cross-sectional study. The goal is to recruit 3500–4000 adults with CHD from 15 countries in five major regions of the world (Asia, Australia, Europe, North and South America). Self-report questionnaires are administered to capture information on PRO domains: (i) perceived health status (12‐item Short‐form Health Survey & EuroQOL-5D); (ii) psychological functioning (Hospital Anxiety and Depression Scale); (iii) health behaviors (Health-Behavior Scale–Congenital Heart Disease); and (iv) quality of life (Linear Analog Scale & Satisfaction With Life Scale). Additionally, potential explanatory variables are assessed: (i) socio-demographic variables; (ii) medical history (chart review); (iii) sense of coherence (Orientation to Life Questionnaire); and (iv) illness perceptions (Brief Illness Perception Questionnaire). Descriptive analyses and multilevel models will examine differences in PROs and investigate potential explanatory variables. Discussion: APPROACH-IS represents a global effort to increase research understanding and capacity in the field of CHD, and will have major implications for patient care. Results will generate valuable information for developing interventions to optimize patients' health and well-being. Registration: ClinicalTrials.gov: NCT02150603.